BIBLIOMETRIC COMPUTATIONAL MAPPING ANALYSIS OF PUBLICATIONS ON FERROUS FERRIC OXIDE (Fe3O4) NANOPARTICLES USING VOSVIEWER - Anisa Noorlela; Asep Bayu Dani Nandiyanto (Mechanical Engineering Department - Institut Teknologi Adhi Tama Surabaya, 2022)
This study aims to analyze computational bibliometric mapping using VOSviewer software on Fe3O4 nanoparticles. The article data was obtained from the Google Scholar database using a reference manager application, namely Publish or Perish. Publish or Perish software is used to conduct a literature review on the selected topic. The title and abstract of the article are used to guide the search process by referring to the keyword “Fe3O4 nanoparticles”. It was found that 998 articles related to the research period used as study material were Google Scholar indexed articles for the last 10 years (2012 to 2022). The results show that Fe3O4 nanoparticles research can be separated into 3 terms: Fe3O4 nanoparticles, nanoparticles, and Fe3O4. The term